|
|
Line 28: |
Line 28: |
| | | |
| Borrowed from http://www.cs.cornell.edu/~asdas/imo/imo/isoln/isoln723.html | | Borrowed from http://www.cs.cornell.edu/~asdas/imo/imo/isoln/isoln723.html |
− |
| |
− |
| |
− | == Solution 2 ==
| |
− | An alternative solution is nested induction in n and m.
| |
− | As induction start we have the case <math>n = 0</math>. In that case <math>m!n!(m+n)! = (m!)^2</math> and <math>(2m)!(2n)! = (2m)!</math>.
| |
− |
| |
− | With induction in <math>m</math> we prove the induction start for <math>n = 0</math> which states that
| |
− |
| |
− | <math>(2m)!</math> is a multiple of <math>(m!)^2</math> for all natural numbers <math>m</math> (including 0) (Assertion 1):
| |
− |
| |
− | For <math>m = 0</math> (induction start) we have <math>(2m)! = 1 = (m!)^2</math>. Hence, we can assume that Assertion 1 holds for <math>m - 1</math> and <math>m > 0</math>: That means that <math>(2m-2)!</math> is a multiple of <math>((m-1)!)^2</math>. Division by <math>(m-1)!</math> leads to the result that <math>X:= (m-1)! = 1 \cdot 2 \cdot \ldots (m-1)</math>
| |
− | is a divisor of <math>M := m \cdot \ldots \cdot (2m-2)</math> and thus <math>X' := mX = 1 \cdot 2 \cdot \ldots m</math>
| |
− | is a divisor of <math>M' := 2m(2m-1)M = m \cdot \ldots \cdot 2m</math>. And so <math>(m!)^2 = m!X'</math> is a divisor of
| |
− | <math>m!M' = (2m)!</math>, which is Assertion 1.
| |
− |
| |
− | Hence, for <math>n = 0</math> as induction start in <math>n</math> the statement holds for all <math>m</math>.
| |
− | So we assume that the statement also holds for all natural numbers <math>n - 1</math>, where <math>n > 0</math>, and all natural numbers <math>m</math> (including 0), which means that
| |
− | we assume that <math>m!(n-1)!(m+n-1)!</math> divides <math>(2m)!(2n-2)!</math> for all <math>m</math>. Division by <math>m!(n-1)!</math> leads to the result that <math>X:= (m+n-1)! = 1 \cdot 2 \cdot \ldots (m + n - 1)</math>
| |
− | is a divisor of <math>M := [(m + 1) \cdot \ldots \cdot 2m] \cdot [n \cdot \ldots \cdot (2n-2)]</math> and thus <math>X' := m!nX = m!(m + n)!</math>
| |
− | is a divisor of <math>M' := m!2n(2n-1)M</math>. And so <math>n!m!(n+m)! = n!X'</math> is a divisor of <math>n!M' = (2m)!(2n)!</math>, which was to prove.
| |
− |
| |
− | [[User:Agentmmk|Agentmmk]] ([[User talk:Agentmmk|talk]]) 16:43, 27 October 2015 (EDT)
| |
Revision as of 02:26, 28 October 2015
Let and be arbitrary non-negative integers. Prove that
is an integer. (.)
Solution
Let . We intend to show that is integral for all . To start, we would like to find a recurrence relation for .
First, let's look at :
Second, let's look at :
Combining,
.
Therefore, we have found the recurrence relation .
We can see that is integral because the RHS is just , which we know to be integral for all .
So, must be integral, and then must be integral, etc.
By induction, is integral for all .
Borrowed from http://www.cs.cornell.edu/~asdas/imo/imo/isoln/isoln723.html